The effect of butterfly hug therapy on stress reduction in the elderly - Maulina, Rinda Dyah; Rasyida, Zulfa Mahdiatur (JOURNAL OF Mental Health Concerns, 2025)
Background: Elderly individuals are vulnerable to stress due to physical, physiological, and psychological changes during the aging process. One intervention used to reduce stress in the elderly is Butterfly Hug therapy, a simple bilateral stimulation technique that is easy to practice and can be done independently. Purpose: To determine the effect of Butterfly Hug therapy on stress reduction in elderly residents. Method: A pre-experimental design with a One Group Pre-Test Post-Test approach. Purposive sampling was used to select 17 respondents. The Perceived Stress Scale (PSS-10) was used as the research instrument. The intervention was conducted three times a week. Results: Data analysis using the Wilcoxon test showed that before the intervention, the minimum stress score was 11, the maximum was 29, and the median was 16.00. After the intervention, the minimum score was 7, the maximum was 22, and the median was 11.00. The test yielded a Z value of -3.644 and a p-value of 0.000. Conclusion: There is a significant effect of Butterfly Hug therapy on reducing stress in elderly residents. Keywords: Butterfly Hug Therapy; Elderly; Stress.